Identifying gene-gene interactions that are highly associated with Body Mass Index using Quantitative Multifactor Dimensionality Reduction (QMDR). Issue 1 (June 2015) - De, Rishika; Verma, Shefali; Drenos, Fotios; Holzinger, Emily; Holmes, Michael; Hall, Molly; Crosslin, David; Carrell, David; Hakonarson, Hakon; Jarvik, Gail; Larson, Eric; Pacheco, Jennifer; et al.
Abstract Background Despite heritability estimates of 40–70 % for obesity, less than 2 % of its variation is explained by Body Mass Index (BMI) associated loci that have been identified so far.Epistasis, or gene-gene interactions are a plausible source to explain portions of the missing heritability of BMI. Methods Using genotypic data from 18, 686 individuals across five study cohorts – ARIC, CARDIA, FHS, CHS, MESA – we filtered SNPs (Single Nucleotide Polymorphisms) using two parallel approaches. SNPs were filtered either on the strength of their main effects of association with BMI, or on the number of knowledge sources supporting a specific SNP-SNP interaction in the context of BMI. Filtered SNPs were specifically analyzed for interactions that are highly associated with BMI using QMDR (Quantitative Multifactor Dimensionality Reduction). QMDR is a nonparametric, genetic model-free method that detects non-linear interactions associated with a quantitative trait. Results We identified seven novel, epistatic models with a Bonferroni correctedp -value of association < 0.1. Prior experimental evidence helps explain the plausible biological interactions highlighted within our results and their relationship with obesity. We identified interactions between genes involved in mitochondrial dysfunction (POLG2 ), cholesterol metabolism (SOAT2 ), lipid metabolism (CYP11B2 ), cell adhesion (EZR ), cell proliferation (MAP2K5), and insulin resistance (IGF1R ). Moreover, we found an 8.8 % increase in the variance in BMI explained by these seven SNP-SNP interactions, beyond what is explained by the main effects of an indexFTO SNP and the SNPs within these interactions. We also replicated one of these interactions and 58 proxy SNP-SNP models representing it in an independent dataset from the eMERGE study. Conclusion This study highlights a novel approach for discovering gene-gene interactions by combining methods such as QMDR with traditional statistics.